LONG-TERM RELATIONSHIPS OF MACROECONOMIC VARIABLES ON INDONESIAN FOREIGN EXCHANGE RESERVES - Antoni Antoni; Akmal Akmal; Irwan Muslim (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2019)
This study aims to prove the long-term relationship of variable onomics to Indonesia's foreign exchange reserves. The data used in this study for 24 years began from 1995 to 2018 using the Error Correction Model (ECM) method. The results of this study indicate that in the short and long term exports and foreign debt have a positive and significant relationship with foreign exchange reserves. The rupiah exchange rate has a negative and significant relationship in the short term, but in the long run has a positiverelationship. Foreign investment has a negative and insignificant relationship in the short term and a positive and insignificant relationship in the long run.Keywords: Foreign exchange reserves, exports, rupiah exchange rate, foreign debt and foreign investment.